Elucidating the modified performance of high nuclearity of Cu nanostructures-PTFE thin film - Nurul Akmal, Che Lah; Murthy, Puhanes (Nature Publishing Group, 2023)
The aim of this study is to attain an extensive insight on the performance mechanism that is associated with the formation of Cu nanostructures- polytetrafluoroethylene (PTFE) thin film. The work presented Cu nanostructures synthesised via microwave-assisted method at different Cu precursor concentrations to observe the influence of different average particle diameter distribution, dm of Cu nanostructures on the fabricated Cu nano thin film. The thin films of Cu nanostructures with a layer of PTFE were fabricated using the Meyer rod coating method. Evaluating the effect of Cu nanostructures at different dm with overcoated PTFE layer showed that the resistance of fabricated thin film coated with PTFE is not significantly different from that of the uncoated thin film. The results implicate the influence of the PTFE layer towards the output performance, which can maintain a stable and constant resistance over time without affecting the original properties of pure Cu nanostructures, although some of the Cu nanostructures seep into the layer of PTFE. The novelty of this study lies in the effect of the intrinsic interaction between the layer of Cu nanostructure and PTFE, which modulate the performance, especially in photovoltaic cell application.